Language Style in Ancur Podcast and Its Utilization as Student Learning Motivation - Fitria, Enggar Anisa; Ali Imron Al Ma’ruf (Universitas Negeri Semarang, 2025)
Generation Z has widely utilized podcasts with various appealing popular languages in the last decade. This research aims to examine the Ancur Podcast about students' learning motivation, as evidenced by the World Top 20 Education Poll forum in 2024, where Indonesia ranked 67th out of 203 countries in the field of education, which is one of the causes of declining student motivation. This study aims to describe the language style used in the conversations of the Ancur Podcast as a medium to motivate students to learn, employing a hermeneutic approach based on Jurgen Habermas's theory. This research utilizes a descriptive qualitative method through observation and note-taking to identify the language styles and the sentences that motivate students in their learning. Based on the analysis results regarding the use of language styles in the Ancur Podcast audio, several figures of speech are employed, such as metaphor, metonymy, euphemism, cynicism, tautology, correction, and exclamation. The percentage of usage for these figures of speech includes metaphor 11%, metonymy 16%, euphemism 37%, cynicism 5%, tautology 5%, correction 11%, and exclamation 16%. The form of motivation obtained from this Ancur Podcast audio consists of information regarding fully funded further education (Bachelor's, Master's, and Doctorate) scholarships, along with guaranteed salaries and promising facilities.